DNA Methylation Pattern and mRNA Expression Level of E-Cadherin and P16 Genes in Thrombotic Disorders - Niloofar Abak M.Sc; Mehdi Azad Ph.D; Fatemeh Mohammad Ali Ph.D; Mostafa Saberian Ph.D; Saeed Turkaman M.Sc; Shaban Alizadeh Prof (Clinical and Applied Thrombosis/Hemostasis, 2024)
Objective DNA methylation, as an epigenetic alteration, plays an essential role in the development of atherosclerosis and venous thrombosis. E-cadherin, a tumor suppressor gene and adhesion molecule, has a crucial function in platelet aggregation and hemostasis. P16, a cell cycle regulator, is involved in venous thrombosis. The aim of this study is to evaluate the DNA methylation patterns and expression levels of the E-cadherin and P16 genes in venous thromboembolism (VTE). Method Peripheral blood samples were collected from 32 patients, including those with deep vein thrombosis (DVT, n = 15), pulmonary embolism (PE, n = 8), DVT with PE (n = 4), intestinal thrombosis (IT, n = 3), and cerebral venous sinus thrombosis (CVST, n = 2), as well as from 10 healthy individuals. The DNA methylation patterns and gene expression levels of E-cadherin and P16 were analyzed using methylation-specific PCR (MSP) and Real-Time PCR, respectively. Results The promoter of the CDH1 gene was partially methylated in 84.4% of thrombotic patients and unmethylated in 15.6% ( P  = 0.183). A significantly higher expression level of CDH1 was observed in the patients compared to the controls ( P  = 0.001). The P16 gene promoter were unmethylated in all control and patient specimens. Compared to normal subjects, the expression level of the P16 was significantly increased in patients ( P  = 0.000). Conclusion Our results indicated that DNA methylation is not the main gene expression regulatory mechanism for E-cadherin and P16 genes in thrombosis. Higher transcription levels of CDH1 and P16 in thrombotic patients may show their crucial roles in the pathogenesis of VTE.